Mucoadhesive Buccal Films Based on Chitosan and Carboxymethylated Feronia Limonia Fruit Pulp Mucilage Interpolymer Complex for delivery of Opioid Analgesics - Patel, Adil (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: To develop and evaluate interpolymer complex (IPC) based buccal mucoadhesive films for delivery of opioid analgesics. The IPC was prepared using Chitosan and carboxymethylated Feronia limonia fruit pulp mucilage. Materials and Methods: In this study, the IPC is formed between mucoadhesive polymer chitosan and carboxymethylated F. limonia fruit pulp mucilage. The resulted IPC is used to prepare buccal mucoadhesive films of a model opioid analgesic. Other excipients include glycerin as plasticizer, a combination of sodium dihydrocholate and ethylenediaminetetraacetic acid sodium salt as permeation enhancers and a backing layer of 1% ethyl cellulose is placed on each film to ensure unidirectional drug release to systemic circulation. The solvent casting method is used to prepare buccal films and evaluated for bioadhesion strength, tensile strength, swelling index, ex vivo diffusion, and in vitro dissolution. Results and Discussion: Formulations are prepared and optimized by 32 factorial design. Formulation F7 was found to be optimized formulation which contained 50 mg drug, 100 mg IPC, and 2% glycerin as plasticizer. Thus, this study suggests that IPC between chitosan and carboxymethylated F. limonia fruit pulp mucilage can act as a potential mucoadhesive polymer system for buccal delivery of opioid analgesic drugs. Conclusion: In this study novel, buccoadhesive film was developed using IPC between chitosan and carboxymethylated F. limonia fruit pulp mucilage. The film was releasing drug over a period of 8-h directly to systemic circulation through buccal mucosa. The extensive first pass metabolism of a drug was prevented to a great extent.